Development and Initial Validation of the Beliefs About Reformed Science Teaching and Learning (BARSTL) Questionnaire. (15th January 2013) - Sampson, Victor; Grooms, Jonathon; Enderle, Patrick
<x xml:space="preserve">Abstract</x> This article describes the development and the initial validation of an instrument that can be used to assess teachers' beliefs about science teaching and learning. The instrument, which is called the Beliefs About Reformed Science Teaching and Learning (BARSTL) questionnaire, draws on the current national science education reform efforts in order to define a traditional‐reformed teaching and learning belief continuum that can be used to map teachers' beliefs. The reliability and validity of the instrument were examined using a multiple perspective approach. The psychometric properties of the BARSTL suggest that it is a valid and reliable instrument for measuring prospective elementary teachers' beliefs about science education.